Candy-Plug Generation II for False Lumen Occlusion in Chronic Aortic Dissection: Feasibility and Early Results. (December 2019) - Eleshra, Ahmed; Kölbel, Tilo; Tsilimparis, Nikolaos; Panuccio, Giuseppe; Scheerbaum, Martin; Debus, E. Sebastian; Mogensen, John; Rohlffs, Fiona
Purpose: To present the early results of false lumen (FL) occlusion in chronic aortic dissection using the Candy-Plug generation II (CP II), which has a self-closing fabric channel that obviates the need for separate occlusion of its center.Materials and Methods: Fourteen consecutive patients (mean age 60±11 years; 10 men) with persistent FL backflow and aneurysm formation at the thoracic segment in chronic aortic dissection underwent thoracic endovascular aortic repair (TEVAR) with FL occlusion using the refined CP II. Primary endpoints were technical success (successful deployment) and clinical success (no FL backflow at the CP II level). Secondary endpoints included 30-day mortality and morbidity and aortic remodeling during follow-up.Results: Technical success was 100%. One patient required additional intraprocedural FL embolization at the CP II level due to persistent FL backflow on final angiography (clinical success 93%), though there was no flow through the CP II center. There were no intraprocedural complications. Immediate complete FL occlusion was achieved in 12 patients; the other 2 required reintervention. One had contrast enhancement in the distal FL proximal to the CP II and was treated with coil embolization. The other patient had persistent type I endoleak at the level of the left subclavian artery (LSA) and underwent left carotid–LSA bypass and proximal stent-graft extension. One patient died due to retrograde type A aortic dissection that was not related to CP II placement. Over a mean 8-month follow-up (range 3–12), 9 patients had computed tomography angiography; 8 patients had evidence of aortic remodeling, while 1 aneurysm sac was stable.Conclusion: The CP II reduces the number of procedural steps and offers good seal, with minimal morbidity and mortality and a high rate of aortic remodeling.